Comparison Study Between Artifacts Lumbal MRI T1 Spin Echo With Pre Saturation And T1 Spin Echo Without Pre Saturation - Made Elisa Deviyanti; Sugiyanto Sugiyanto; Rini Indrati (Jurnal Riset Kesehatan, 2012)
This study is an experimental study, data collected by observation. Data processed by the Friedman test and Wilcoxon test. From the results of this research note there is a difference between Spin Echo T1 artifact lumbar MRI with pre saturation and Spin Echo T1 without pre-saturation. These results can be seen from the average value of the overall test Friedman test with p value less than 0.001 in axial cuts and sagittal cuts. Then the ratio of artifacts to see the value of the Wilcoxon test performed two variables, to determine the differences of each placement pre saturation. Values obtained in the setting of artifacts terkecul Anterior presaturasi in both sagittal and axial to pieces.